Socializing Multiculturalism Ideology through Multicultural Education: Potentials in History for High Schools - Een Syaputra (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
The formulation of this article was motivated by a classic problem inIndonesia related to diversity in race, gender, political ideology, religion,social class which become an obstacle for the creation of socialintegration even cause various conflicts, both vertically and horizontally.Confronted with the issue, then, multicultural education as an attempt topromote the ideology of multiculturalism, in which there are principles touphold fraternity, justice, respect, and acknowledge differences becomevery important to be applied in education. Especially for the subjects ofhistory, it has a big opportunity to do. There are many historical learningmaterials that can be used as a foothold to embed the principles ofmulticulturalism to students.Keywords: Multiculturalism, Multicultural Education, History for High Schools